g+3.5g=11-0.5g

Simple and best practice solution for g+3.5g=11-0.5g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+3.5g=11-0.5g equation:


Simplifying
g + 3.5g = 11 + -0.5g

Combine like terms: g + 3.5g = 4.5g
4.5g = 11 + -0.5g

Solving
4.5g = 11 + -0.5g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '0.5g' to each side of the equation.
4.5g + 0.5g = 11 + -0.5g + 0.5g

Combine like terms: 4.5g + 0.5g = 5g
5g = 11 + -0.5g + 0.5g

Combine like terms: -0.5g + 0.5g = 0.0
5g = 11 + 0.0
5g = 11

Divide each side by '5'.
g = 2.2

Simplifying
g = 2.2

See similar equations:

| 8(x+2)=32+7x | | -3+17x=52+6x | | 98x-7=1 | | g+3.59g=11-.5g | | 10(s-6)=-137 | | 4(t+2)=8 | | -20=4y+8 | | 1+8=-64x+45 | | -5+3(X+4)=33 | | (3x^2)+2x+6=50 | | 2+x=5-6x | | 6n+7=2n+25 | | 8x+821=3 | | 3+4(X-5)=9 | | X^2-4y^2-4x-24y-48=0 | | 7-3p=p+7 | | 2/3x-4/5=1/2x | | 18=1.31(1985)-2581.6 | | cos(2x)-3cos(x)=2 | | 28=8x-1 | | 4(4s+4)=64 | | 5(t-4)+3t=4(2t+3)-11 | | 7x-4(x+4)+20=20 | | 4(4s+7)=124 | | 3y+22=16.6 | | 3x-39=90 | | 5x+2=6-x | | 24a-22=4-24a | | (6x+2)=180 | | (U-8)*8=80 | | 3(2l+4)=66 | | 2(3a-4)+6=8(a+1) |

Equations solver categories